(untitled) (The Gaze: Journal of Tourism and Hospitality, 2016)
An image on tourism industry products gives potential traveller an important sense of emotional security. They can establish harmonious relationship between themselves and the outside world. National image is a long term investment and should be considered every time a decision is made at high or low levels of management. Marketers of the tourism product should not underestimate the value of a national image and its effect upon tourist behaviour. The steady growth in the world tourism market has earmarked its importance globally. Inevitably such tourism activities have an impact on wider economies, in both the developed and the developing world. Realizing the fact and importance of tourism, there is growing awareness worldwide. However, there is still relatively little appreciation of the specific operating characteristics of tourism firms, and especially of tourism entrepreneurship within developing countries. The development of national tourism policies, long-term tourism master plans, and tourism marketing strategies clearly highlights the significance that governments all over the world are attached and giving utmost priority to the industry. It is equally important to understand that the reliance on international tourism as a strategy for economic development might be precarious for the country. This is justified by the fact that it is so often associated with a dependency upon external sources of growth. This type of situation will be observed by those countries, which will be having their internal political conflicts, or in other socio-political tribulations. Therefore, such external sources at that time tend to be fickle in nature. Tourism being very sensitive and psycho graphic industry, choices of tourist destinations is susceptible to large fluctuations, particularly because of economic conditions in the tourist’s country of origin or the political situation in the holiday destination. Likewise, there also exist significant socio-economic and geographical dimensions of tourism dependency. The growth of the tourist industry and its potential for stimulating economic development through service sectors has contrived an important point in much of the literature on tourism. South Asian Sub-regional countries are considering tourism as an important industry for their livelihood. Different concepts and different philosophies on tourism are gaining wider recognition in this sub-region. That is why, research and studies going on widely into these areas. However, regardless of considerable dispute on the subject there is still little conformity as to tourism’s role in economic development where the governments will be having many more other socio-economic obligations. In such countries, the overall picture of tourism’s role is found to be somewhat blurred with some challenges, not only by the different assessments of economic development, but also by its socio-cultural and environmental implications as well. The Gaze: Journal of Tourism and Hospitality Vol.6 2014 pp.70-97